2022
DOI: 10.30964/auebfd.1020589
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Web 2.0 Supported Assessment and Evaluation Training on Questions Developed by Pre-Service Teachers

Abstract: It was aimed to determine the effect of "Web 2.0 supported measurement and evaluation training" (WSMAT) on the content and form properties of the questions developed by pre-service science, mathematics and social studies teachers. For this purpose, pre-service teachers were received a total of 40 hours training for 5-days to utilize web 2.0 tools used for the measurement and evaluation purposes. Pre-service teachers were asked to develop exam questions consisting of 30 questions by using traditional methods b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As a result of the study, it was concluded that the teachers were aware of Web 2.0-based applications, they used these applications in their lessons, they benefited from Web 2.0-based applications while making assessments and evaluations, and they advised their other colleagues to use them as well. Çelenk and Tatlı (2022), in their study, investigated the effects of Web 2.0 supported measurement and evaluation tools on the form and structure characteristics of the questions developed by pre-service science, mathematics and social studies teacher candidates. A total of 30 pre-service teachers studying in the 3rd and 4th grades participated in the research.…”
Section: Findings and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the study, it was concluded that the teachers were aware of Web 2.0-based applications, they used these applications in their lessons, they benefited from Web 2.0-based applications while making assessments and evaluations, and they advised their other colleagues to use them as well. Çelenk and Tatlı (2022), in their study, investigated the effects of Web 2.0 supported measurement and evaluation tools on the form and structure characteristics of the questions developed by pre-service science, mathematics and social studies teacher candidates. A total of 30 pre-service teachers studying in the 3rd and 4th grades participated in the research.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…Web 2.0 supported applications also contribute to technology literacy (Çelenk & Tatlı, 2022). Web 2.0 supported applications also show positive effects in areas such as mutual cooperation, improvement in communication skills, and individual multi-faceted development (Eyüp, 2022).…”
Section: Introductionmentioning
confidence: 99%